A Transformative Innovation Model Framework for New Product Development - Al Husban, Mallak (2021)
Given the current digital revolution, there is an increasing need for emerging firms to utilize the emerging technological tools while containing their disruptive effects and alleviating workforce command and knowledge of the new ‘digital’ environment. While it is known that innovation is crucial for survival and growth, the various challenges SMEs face on all fronts call for a change in the conventional, often lengthy, innovation processes where they are no longer at a disadvantage and at risk. Hence, this dissertation offers a practical definition and overall understanding of the new proposed Transformative Innovation Model and the practical steps for organizations to harness the emerging technologies to transform their existing products into radically new ones with distinct features and patent protection, displacing larger corporations in an existing market. The dissertation takes several questions into consideration; what are the similarities and differences between the new model and existing innovation models, which shortcomings does the new model address and how can enterprises follow suit with their own transformative innovation. Ultimately, this dissertation identifies the key features of transformative innovation, proposes a refined framework for adopting the model, originally constructed by Li and Tan (2017) and offers two contemporary real-life projects that undergo transformative innovation.